ANALISIS PENDEKATAN FONETIK DALAM PROGRAM PEMBELAJARAN AL-QUR’AN UNTUK MENINGKATKAN KEFASIHAN MEMBACA SISWA DI MTSN 15 JOMBANG - Putri Nabila Norhliza; Aida Arini (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The low level of Quranic reading proficiency among some students is one of the challenges in learning, particularly regarding the accuracy of letter pronunciation and the application of tajwid rules. Based on observations at MTsN 15 Jombang, students’ Quranic reading proficiency varies widely, necessitating a more effective and targeted teaching approach. This study aims to analyze the application of the phonetic approach in the Quran learning program to improve students’ reading fluency at MTsN 15 Jombang. This study employs a descriptive qualitative approach. Data collection techniques were conducted through observation, semi-structured interviews, and documentation. The data sources for this study were the principal, teachers, and students. Data analysis was conducted through data reduction, data presentation, and verification or drawing conclusions. The research findings indicate that the phonetic approach can help improve students’ fluency in reading the Qur’an through a gradual, systematic learning process tailored to students’ needs. Teachers provide examples of letter pronunciation, individual reading practice, and additional guidance for students who struggle to distinguish the sounds of the Hijaiyah letters and the rules of tajwid. In addition to improving reading skills, this approach fosters discipline, etiquette, and religious character in students throughout the learning process. The program’s success is supported by teacher competence, flexible and interactive teaching methods, and a religious school environment, although some challenges remain, such as varying student abilities and limited class time.